Образ идеального ученого у современной российской молодежи - Razina, Tat'yana V.; Volodarskaya, Elena A. (Rossijskij psihologičeskij žurnal., 2017)
Introduction. Studying the image of an ideal scientist among modern young Russians is important for understanding their professional preferences and desire to engage in scientific activities in modern conditions of science. The research concentrates on structural and substantial characteristics of the image of a scientist among students and working young people, and also their factors. Materials and Methods.The stages of the research included methods of semantic differential, laboratory experiment, and factor analysis. Results. The main stage of the research made it possible to construct the semantic space reflecting the characteristics of the images of an ideal scientist and various cinematographic images of scientists among students and working young people. The image of an ideal scientist had cognitive (ability to formulate problems and express ideas, tolerance for uncertainty, and the discipline of thinking) and personal (purposefulness, resoluteness, adherence to principle, focus on results, high working capacity, versatility, originality, rich imagination) qualities. Discussion. The students for whom the assimilation of scientific knowledge is the basis for educational activities construct the image of a scientist being guided by their knowledge about real scientists and the idea about scientific activity as a thinking and intellectual work. Assessing cinematographic images reflects this. Working young people have a lack of scientific research in the content of professional activity; they are estranged from scientific reality and suffer from a lack of objective information. Thus, working young people construct the image of a scientist on the basis of their representations about scientists and also cinematographic images, reflecting stereotypes of scientists (often through demonstrating the tools of scientific work). This testifies to the simplification of the image of a scientist among working young people. Substantial characteristics of the image of an ideal scientist are analogous among working and studying young people. However, the image forming foundation differs in the two studied groups. Введение. Авторами доказывается актуальность изучения образа идеального ученого у современных молодых россиян для понимания формирования их профессиональных предпочтений и желания заниматься научной деятельностью в современных условиях функционирования науки. Новизна исследования заключается в установлении структурно-содержательного своеобразия имиджа ученого у студентов и работающей молодежи, и факторов, его обуславливающих. Материалы и методы. В разделе описываются подготовительный и основной этапы исследования, которые включали в себя методы семантического дифференциала, лабораторного эксперимента, факторного анализа. Результаты. Основной этап исследования позволил смоделировать семантическое пространство, отражающее характеристики образов идеального ученого и различных кинематографических образов ученых в сознании студентов и работающей молодежи. Образ идеального ученого характеризуется когнитивными (способность формулировать проблему, выражать свои мысли, устойчивость к неопределенности, дисциплина мышления) и личностными (целеустремленность, решительность, принципиальность, нацеленность на результат, высокая работоспособность, разносторонность, неординарность, богатая фантазия) качествами. Обсуждение результатов. Авторы показывают, что студенты, для которых усвоение научных знаний выступает основой образовательной деятельности, конструируют образ ученого с опорой на свои знания о реальных научных работниках и на представления о научной деятельности как о мыслительной, интеллектуальной работе, что отражается в оценке кинематографических образов. Работающая молодежь, в силу отсутствия научного поиска в содержании профессиональной деятельности, отдаленности от актуального положения дел в науке, испытывает дефицит объективной информации и конструирует образ ученого на своих прошлых представлениях о научных работниках, а также кинематографических образах, отражающих стереотипные представления об ученых (чаще через демонстрацию средств научного труда). Это говорит об упрощении образа ученого у работающей молодежи. В заключение делается вывод о содержательной схожести образов идеального ученого у работающей и учащейся молодежи, и отличиях в его имиджформирующей основе.